2016
DOI: 10.1177/1971400916678229
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia-treated neonates with hypoxic-ischemic encephalopathy: Optimal timing of quantitative ADC measurement to predict disease severity

Abstract: To determine the optimal time window for MR imaging with quantitative ADC measurement in neonatal HIE after hypothermia treatment, a retrospective review was performed on consecutive hypothermia-treated term neonates with HIE, with an initial and follow-up MR imaging within the first two weeks of life. Three neuroradiologists categorized each set of MR imaging as normal, mild, moderate or severe HIE based on a consensus review of the serial imaging. The lowest ADC values from the white matter, corpus callosum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…30 The optimal timing for DWI in HIE is 3e7 days, after which pseudonormalization can occur. 31 Magnetic resonance spectroscopy (MRS) sequences can have additive prognostic information, but were not systematically performed in our patients. 32 In infants treated with HT, early (day 4) versus late MRI (!1 week) both yielded 100% sensitivity for adverse outcome at age two years, but early MRI had a higher specificity.…”
Section: Discussionmentioning
confidence: 99%
“…30 The optimal timing for DWI in HIE is 3e7 days, after which pseudonormalization can occur. 31 Magnetic resonance spectroscopy (MRS) sequences can have additive prognostic information, but were not systematically performed in our patients. 32 In infants treated with HT, early (day 4) versus late MRI (!1 week) both yielded 100% sensitivity for adverse outcome at age two years, but early MRI had a higher specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion abnormalities tend to evolve over time, starting as more localized findings in the first 48 h, becoming more diffuse and apparent by day 4-5, and then pseudo-normalizing about 7 days after birth. Infants treated with TH demonstrate more delayed pseudo-normalization around 8-10 days after birth [67,74]. Apparent diffusion coefficient values have also been correlated with favorable or unfavorable outcomes [69,[75][76][77].…”
Section: Reliability and Predictive Value Of Us Findingsmentioning
confidence: 98%
“…Second, previous studies have described pseudo-normalization of diffusion weighted imaging and apparent diffusion coefficient maps in neonates with HIE as early as 4 days after the insult and suggested that neonates who are scanned after the first week of life may exhibit false-negative results [ 21 ]. We included MRIs obtained up to 10 days of life, which is on the later end of the optimal time window [ 11 ]. However, this is unlikely to change our outcome because our MRIs were obtained on an average of 6 days of life, and the splenial abnormality group had scans done on average at a higher day of life than the no splenial abnormality group.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with the diagnosis of HIE, therapeutic cooling performed, and MRI obtained within the first 10 days of life were included. Neonates whom MRI studies were obtained beyond 10 days of life were excluded to prevent the phenomenon of “pseudo-normalization” to confound our findings [ 11 ]. Neonates without MRI studies, lacking documentation of HIE, unqualified for therapeutic cooling, or transferred to our facility later than day of life 1 were excluded as well.…”
Section: Methodsmentioning
confidence: 99%